2020
DOI: 10.17392/1189-20
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year risk assessment for type 2 diabetes mellitus using the Finnish Diabetes Risk Score in family medicine

Abstract: <p><strong>Aim<br /></strong> To assess ten-year risk of diabetes mellitus type 2 (T2DM) using the Finnish Diabetes Risk Score (FINDRISC) in respondents over 18, in Primary Health Centre in Banja Luka.<br /><strong> Methods</strong> <br />A prospective study was conducted using data from a population with undiagnosed T2DM in Primary Health Centre in Banja Luka. Eligible respondents were those aged 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…In the same sense, Barreto et al [ 24 ] also reported a higher prevalence of T2D in older age groups, specifically 19% in the 55–64 years old group and 23.8% in the 65–74 years old group. Indeed, most rates in epidemiology and demography are strongly age-dependent (e.g., incidence, prevalence, and mortality) [ 18 , 48 , 49 ]; therefore, the findings of this study are congruent with the reported age-related impact.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the same sense, Barreto et al [ 24 ] also reported a higher prevalence of T2D in older age groups, specifically 19% in the 55–64 years old group and 23.8% in the 65–74 years old group. Indeed, most rates in epidemiology and demography are strongly age-dependent (e.g., incidence, prevalence, and mortality) [ 18 , 48 , 49 ]; therefore, the findings of this study are congruent with the reported age-related impact.…”
Section: Discussionsupporting
confidence: 85%
“…When the FINDRISK score is applied, the risk of developing T2D appears to be higher for men than women, specifically moderate risk (18.4% vs. 17.2%) and high risk (12.2% vs. 10.6%). Previous reports in other specific populations had demonstrated an increased risk of T2D for women by applying the FINDRISK score [ 35 , 49 ]. This diabetes risk score has shown validity for predicting the development of T2D in the next 10 years [ 34 ].…”
Section: Discussionmentioning
confidence: 99%